KELAYAKAN EKONOMI DAN RESPON PETANI TERHADAP VUB PADI GOGO DAN SISTEM LARGO DI KABUPATEN POSO SULAWESI TENGAH - Heni SP Rahayu; Masyitah Muharni; Andi Baso Lompengeng Ishak (Politeknik Pembangunan Pertanian Medan, 2020)
The potential of dry land in Central Sulawasi is an alternative for increasing rice production within the limited area for rice planting. However, the productivity of dry land is currently still low because of improper cultivation. One of the efforts to increase productivity is the introduction of technological innovation in the largo planting line system and the upland rice cultivation of new superior varieties. However, the new technology is not necessarily in accordance with the preferences of farmers that influence the level of technology adoption. The study aims to know economic feasibility and farmer response toward introduction of the New Superior Variety (VUB) and largo planting line system in Poso District Central Sulawesi Province. The approach of study is a qualitative research which purposively choose 20 cooperator farmer as respondent of the survey. Farmers' response to new technological innovations is measured by scoring method, while its ecomomic feasibility is determined by feasibility margins of existing and introduced technology. The results showed that farmers interested to VUB components and the largo system. Those technology are needed by farmers and easy to be implemented in field. The characteristics of VUB namely Inpago 11 and Situ Bagendit are generally favored by farmers. The results of Marginal Benefit Cost Ratio (MBCR) show that the introduction of technology used the largo system and dry land VUB is more economically profitable with MBCR 1.67